2021
DOI: 10.3389/fmicb.2021.672837
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Distribution of Rotavirus Genotypes Among Children With Acute Gastroenteritis in Areas Other Than Java Island, Indonesia, 2016–2018

Abstract: Group A rotaviruses (RVAs) are the leading cause of acute gastroenteritis, which is often associated with severe symptoms in children under 5 years old. Genetic reassortments and interspecies transmission commonly occur, resulting in a great diversity of RVA circulating in the world. The aim of this study is to determine the prevalence and distribution of RVA genotypes among children in Indonesia over the years 2016–2018 across representative areas of the country. Stool samples were collected from 202 pediatri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
(55 reference statements)
0
5
0
Order By: Relevance
“…Several publications have reported the emergence of the G9 genotype in other countries during approximately the same period. A study performed in 2018 in the West Nusa Tenggara region of neighboring Indonesia detected the presence of G9P[8] strains; however, these strains were absent in South Sumatra and West Papua [ 32 ], indicating a localized emergence of this genotype. Furthermore, a study carried out in 2017–2018 in China showed G9P[8] to be the predominant strain [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several publications have reported the emergence of the G9 genotype in other countries during approximately the same period. A study performed in 2018 in the West Nusa Tenggara region of neighboring Indonesia detected the presence of G9P[8] strains; however, these strains were absent in South Sumatra and West Papua [ 32 ], indicating a localized emergence of this genotype. Furthermore, a study carried out in 2017–2018 in China showed G9P[8] to be the predominant strain [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is different from previous reports, which identified Rotavirus as the most common pathogen in HIV-negative children with acute diarrhea [ 12 13 ]. The prevalence of pediatric diarrhea caused by Rotavirus infection remains high in Indonesia particularly in children <5 years old [ 14 ]. The absence of a national program for Rotavirus vaccine along with the presence of mostly HIV-negative subjects in this study (under 6 years old) explain the supposedly high prevalence of diarrhea associated with Rotavirus infection.…”
Section: Discussionmentioning
confidence: 99%
“…The expressions of HBcAg recombinant protein in bacteria [18][19][20] and yeast [21][22][23] have been reported in various studies. In this study, we report the expression of HBcAg protein derived from HBV sub-genotype B3, one of the predominant sub-genotypes in Indonesia [24][25][26][27][28], in Lactococcus lactis.…”
Section: Introductionmentioning
confidence: 99%